Fenofibrate exerts protective effects against gentamicin-induced toxicity in cochlear hair cells by activating antioxidant enzymes - Park, Channy (Int J Mol Med, 2017)
Fenofibrate, an activator of peroxisome proliferator-activated receptors (PPARs), has been shown to protect the kidneys and brain cells from oxidative stress; however, its role in preventing hearing loss has not been reported to date, at least to the best of our knowledge. In this study, we demonstrated the protective effects of fenofibrate against gentamicin (GM)-induced ototoxicity. We found that the auditory brainstem response threshold which was increased by GM was significantly reduced by pre-treatment with fenofibrate in rats. In cochlear explants, the disruption of hair cell layers by GM was also markedly attenuated by pre-treatment with fenofibrate. In addition, fenofibrate almost completely abolished GM-induced reactive oxygen species generation, which seemed to be mediated at least in part by the restoration of the expression of PPAR-α-dependent antioxidant enzymes, including catalase and superoxide dismutase (SOD)-1. Of note, fenofibrate markedly increased the expression of heme oxygenase-1 (HO-1) which was also induced to a certain degree by GM alone. The induced expression of HO-1 by fenofibrate appeared to be essential for mediating the protective effects of fenofibrate, as the inhibition of HO-1 activity significantly diminished the protective effects of fenofibrate against the GM-mediated death of sensory hair cells in cochlea explant culture, as well as in zebrafish neuromasts. These results suggest that fenofibrate protects sensory hair cells from GM-induced toxicity by upregulating PPAR-α-dependent antioxidant enzymes, including HO-1. Our results provide insight into the preventive therapy for hearing loss caused by aminoglycoside antibiotics.